Knowledge, attitudes and practices among populations exposed to bats in southern Nigeria - Osinubi, M. O. V.; Recuenco, S.; Kuzmin, I.; Haberling, D. L.; Blau, D. M.; Davis, L. B.; Ehimiyein, A. M.; Ogunkoya, A. B.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Among the currently recognized species in the Lyssavirus genus worldwide, all but one (Mokola virus) has been identified in bats. Recent discovery of emerging pathogens of zoonotic importance in bats raises concerns about health risks of populations that directly or indirectly come in contact with these diverse mammals. Idanre, an ancient city situated in Southwest Nigeria, conducts a unique bat festival twice annually, where the populations have traditional practices that involve capturing and consuming bats. These activities bring them into direct contact with bats that are important not only because of potential exposure to lyssaviruses, but also to other emerging pathogens. A knowledge, attitude and practices survey was developed and administered to investigate the potential risk of exposure to emerging diseases among these populations living around bat caves, as well as those who participate in the bat festival. Serum samples were collected from humans and bats in the study area, and were analyzed for lyssaviruses and other potential microorganisms. Participants (n=142) were recruited from 90 households in 5 different communities (4 rural and 1 urban). Participant ages ranged between 9 – 83 years. Twenty-one (28%) participants claimed to have participated in the bat festival and 15 (71%) participated twice a year. Of those that participated in the festival, 14 (67%) were involved in multiple activities: 14 (67%) reported involvement in bat preparation/consumption, 12 (75%) hunted bats, 4 (19%) sold bats, and 5 (24%) watched the events. Thirty (26%) study participants claimed to have entered a bat cave and 53 (50%) touched a live bat. Eighteen (18%) participants who reported direct contact with bats also reported scratches and 14 (15%) reported bat bites. Ninety-three participants (92%) made no attempt to protect their families from bat bites, while 5 (5%) prevented bats from entering the home, and 1 (1%) reported destroying bats entering the home. Only 10 (15%) participants claimed to have an extensive knowledge of rabies. However, 33 (53%) would do nothing if bitten or scratched by a bat. A total of 102 blood samples were collected from humans. Neutralization against rabies virus was detected in 3 (3%). There was no evidence of neutralization against non-rabies lyssaviruses. Among the 145 bat sera, seroprevalence of Lagos Bat Virus (LBV) antibodies was observed in Rousettus aegyptiacus (51%) and Eidolon helvum (24%) species. Some of the LBVpositive samples additionally neutralized Shimoni bat virus (SHIBV). Our results indicate an insufficient knowledge about rabies among the study population and an increased exposure through practices and attitudes towards bats, that maybe harboring unknown zoonotic pathogens. This calls for plans to provide continuous surveillance of important pathogens of risk to human health, and the need to have preventive measures and response strategies in place to safe-guard human health.